Theologies of Liberation in Palestine-Israel Indigenous, Contextual, and Postcolonial Perspectives. - Masalha, Nur.; Isherwood, Lisa. (Havertown : The Lutterworth Press, 2014)
This collection concerns the development of contextualised theologies of liberation in Palestine and as part of the indigenous Palestinian people's struggle for justice and liberation. The work is innovative because of its inclusion of indigenous perspective within its remit and the introduction of new concepts such civil liberation theology. The collection offers other ways to look at biblical discourses and their impact on the ongoing conflict, ways to live peace, ways to be ethical when visiting these conflicted lands, understandings of resource ethics and even a new way to understand how w.
4. Reading the Bible with the Eyes of the Philistines, Canaanites and Amalekites: Messianic Zionism, Zealotocracy, the Militarist Traditions of the Tanakh and the Palestinians (1967 to Gaza 2013)5. God's Mapmakers: A Theology of Dispossession; 6. The Quest for Peace with Justice in the Middle East: Christian Zionist and Palestinian Theologies; 7. Transcending Monotheism and a Theology of Land; 8. Beyond Interfaith Reconciliation: A New Paradigm for a Theology of Land; 9. Confronting the Truth: New Awakenings to the Palestinian Situation.
Print version record.
10. Civil Liberation Theology in Palestine: Indigenous, Secular-Humanist, and Post-Colonial PerspectivesBack Cover.
Master record variable field(s) change: 072
Keywords: Love -- Biblical teaching; Liberty; Redemption; Messiah -- Judaism; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Liberty; Love -- Biblical teaching; Messiah -- Judaism; Redemption; RELIGION / Religion, Politics & State; Electronic books